Electrocardiographic markers of hypertrophy in children: revisiting R/S overlap and the Katz-Wachtel phenomenon - Owsianka, Nikola; Schober, Lukas; Sallmon, Hannes; Scherr, Daniel; Köstenberger, n; Manninger, Martin; Öffl, Nathalie; Kurath-Koller, Stefan (Frontiers in Pediatrics, 2025)
BackgroundMany children show R/S overlap in ECG chest leads. The Katz-Wachtel phenomenon, described in the 1960s, characterizes high R and S waves ≥50 mm as an ECG feature of biventricular cardiac hypertrophy. This study investigates the KWP and the association between an R/S overlap and cardiac hypertrophy.MethodsRetrospective study including 800 pediatric patients, treated at the Division of Pediatric Cardiology, University Hospital Graz, between 2016 and 2022. ECG measurements with regard to R/S overlap and voltage in chest leads and review of echocardiography findings of cardiac hypertrophy. ECG measurements were manually obtained and reviewed by two blinded pediatric cardiologists.ResultsOf the 500 patients with an R/S overlap, 4% had confirmed cardiac hypertrophy compared to 1% of children without confirmed R/S overlap. Sensitivity was highest in leads V3/4 (69%), while specificity was highest in leads V1/V2 (93%) and V5/V6 (96%), respectively. A statistically significant correlation between R/S overlap and hypertrophy was found.ConclusionR/S overlap correlates with myocardial hypertrophy in children. While it demonstrates high sensitivity, its limited specificity prevents its use as a standalone diagnostic parameter. It may contribute to early identification when combined with other ECG features and echocardiographic evaluation.